2020
DOI: 10.1097/md.0000000000021141
|View full text |Cite
|
Sign up to set email alerts
|

A study for precision diagnosing and treatment strategies in difficult-to-treat AIDS cases and HIV-infected patients with highly fatal or highly disabling opportunistic infections

Abstract: Background: Toxoplasma encephalitis (TE) is one of the main opportunistic infections in acquired immunodeficiency syndrome (AIDS) patients, and represents a social burden due to its high prevalence and morbidity. Concomitant antiretroviral therapy (ART), together with effective anti- toxoplasma combination therapy, is an effective strategy to treat AIDS-associated TE (AIDS/TE) patients. However, the timing for the initiation of ART after diagnosis of TE remains controversial. We therefore designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Patients with TBM and cryptococcal meningitis had short survival and high mortality rates. The intermittent availability of serum cryptococcal antigen (CrAG) tests, first-line fungicidal (amphotericin-based) regimens for cryptococcal meningitis, rapid diagnosis tests (Xpert MTB), and drugs to treat XDR TB may have resulted in increased morbidity and mortality (Hanif et al 2022 ; Okurut et al 2020 ; Zeng et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with TBM and cryptococcal meningitis had short survival and high mortality rates. The intermittent availability of serum cryptococcal antigen (CrAG) tests, first-line fungicidal (amphotericin-based) regimens for cryptococcal meningitis, rapid diagnosis tests (Xpert MTB), and drugs to treat XDR TB may have resulted in increased morbidity and mortality (Hanif et al 2022 ; Okurut et al 2020 ; Zeng et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies under controlled conditions to generate evidence are needed to corroborate these findings. Future research also needs to address the chronic complications of those who manage to survive ANI secondary to HIV/AIDS and OIs and provide insights into cognitive and physical disabilities and rehabilitation (53).…”
Section: Discussionmentioning
confidence: 99%
“…In a phase IV, multicenter, prospective, randomized open-label clinical trial, Schafer et al found similar safety between immediate (within 7 days) and deferred (after completing OI-therapy) for starting antiretroviral therapy in cerebral toxoplasmosis patients (3–6 weeks) [ 54 ]. A randomized controlled trial is ongoing to evaluate the optimal timing for HAART in PLWH with cerebral toxoplasmosis ChiCTR1900021195 [ 55 ]. Wang et al reported that most HAART compounds had no significant interaction with sulfadiazine and pyrimethamine [ 56 ].…”
Section: Treatmentmentioning
confidence: 99%